Study of the Factors Influencing the Outcome of In Vitro Fecondation at the Pays D'aix Hospital Centre - TOGNIFODE, Véronique; ABOUBAKAR, MOUFALILOU; COOVI, Foreck Ménélas Bignon; HOUNKPONOU-AHOUIGNAN, Fanny; LOKOSSOU, Mègnissè Sèna H. S.; DANGBEMEY, Djima Patrice; Gayito, Adagab Rene Ayaovi; HOUNKPATIN, BENJAMIN IGNACE B.; DENAKPO, Justin Lewis (My University, 2022)
Objective: To analyze the results of five years of In Vitro Fertilization (IVF) practice in the medically assisted procreation unit of the gynecology department of the Center Hospitalize du Pays d ́Aix. Materials and methods: This was a retrospective study for descriptive and analytical purposes covering a period of five years from January 1, 2014 to December 31, 2018. It focused on patients treated for In Vitro Fertilization (IVF) in the unit of medically assisted procreation of the gynecology department of the Center Hospitalier du Pays d'Aix. Result: At the end of this study, the data completion rate was on average 94%. The mean age of the patients was 35 years with extremes of 25 years and 44 years. This was a generally non-smoking (76.7%) and 90.1% non-obese population. Infertility was secondary in 58% of cases. Male causes accounted for 22% of the indications for In Vitro Fertilization (IVF). With regard to female infertility, there is a homogeneous distribution between endometriosis (27%), tubal (21%), cervical (18%), ovulatory (18%) and unexplained (21%) causes. The main prognostic factor turned out to be age. Conclusion: Infertility is a couple's business, not just a woman. Our study showed that age was the main prognostic factor influencing the outcome of In Vitro Fertilization (IVF) with a decrease in the chances of success with increased age.
Keywords: Fertilization; Procreation; Infertility; Prognosis